Korelasi Hasil Belajar Aqidah Akhlak Dengan Kepatuhan Pada Tata Tertib Sekolah di MAN 2 Bukittinggi - Simatupang, Ardiansyah; Aprison, Wedra (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This research is motivated by the results of learning high moral aqidah which is related to student compliance with school rules, but there are still some students who violate the rules and regulations. Therefore, researchers are interested in researching the correlation between learning outcomes of moral aqidah and compliance with rules at MAN 2 Bukittinggi. The problem formulation in this research is: Is there a significant correlation between the results of learning moral aqidah with obedience to rules and regulations? This study aims to determine Correlation between learning outcomes of moral aqidah and compliance with school rules and regulations at MAN 2 Bukittinggi. The hypothesis in this research is that there is a sufficient correlation with a level of 0.555 between the learning outcomes of moral aqidah with his compliance with school rules at MAN 2 Bukittinggi.The type of research used is correlational research. The population of this study was all class XI IPA MAN 2 Bukittinggi, totaling 149 students from five classes, with a sample of 30 students. This research data in the form of a questionnaire regarding compliance with the rules. The research results obtained r = 0.555 at a sufficient level. This shows that Ho is rejected and Ha accepted, which states that there is sufficient correlation between learning outcomes of aiqdah morals and obedience on school rules and regulations at MAN 2 Bukittinggi.